THE IMPACT OF DIGITAL MARKETING STRATEGIES ON CUSTOMER SATISFACTION AND LOYALTY-APPLIED RESEARCH AT ZAIN TELECOM COMPANY IN IRAQ - Omar Karim Kazem (Scholars Digest Publishing, 2024)
The researchers said that the study explored the impact of digital marketing strategies on customer satisfaction and loyalty in various dimensions (research marketing, social media marketing, email marketing, mobile marketing) through its application to Zain Telecommunications Company in Iraq. It has become one of the most essential practices in managing the buying and selling process. The study's primary purpose is to measure customer satisfaction with Zain Telecom Iraq services and understand the impact of digital marketing strategies on their satisfaction. Using a sample of customers engaged in digital marketing practices, the study showed that increased customer satisfaction increases their loyalty to the company and the continuity of their business relationship. The quality and reliability of a product or service are some of the most important factors affecting customer satisfaction. Good and excellent customer service is vital in increasing customer satisfaction and loyalty. There is a strong connection between effective communication with customers and customer satisfaction and loyalty. To achieve the purpose of the study, the researcher made suggestions. The company must be committed to providing high-quality and reliable products or services. This can be achieved by reviewing and improving processes and leveraging industry best practices. Ongoing training and development should be provided to employees who interact with customers. You must have the skills and knowledge to provide quality service and resolve problems effectively.
Keywords: Digital Marketing Strategies, Customer Satisfaction, Zain Telecom, Iraq.